2015
DOI: 10.4028/www.scientific.net/amr.1119.29
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of AZO Film Deposited by RF Powered Magnetron Sputtering System

Abstract: This paper investigates the dependence of pressure onto characteristic of Aluminium Zinc Oxide (AZO) thin films. Films were deposited on a glass substrate by RF Magnetron Sputtering using AZO ceramic target with 99.99% purity. Sputtering was performed with RF power of 100 Watt and the deposition times were fixed at 40 minutes. The argon pressures were varied from 10 sccm to 30 sccm in order to achieve different working pressure during deposition in order to study the effect of pressure towards characteristic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Wu et al 21 reported that the grain size declined with increasing gas flow, the highest grain size was 33.72 nm, recorded at 40 sccm, and that it decreased to 18 sccm for a flow rate of 60 sccm argon flow rate. The decrease in grain size from 28.85 to 23.43 nm with the rise in argon flow rate from 10 to 30 sccm was also observed by Shain et al 23 . A similar increase in grain size of thin films from 6.3 to 14.8 nm with a decrease in argon flow rate was also observed by Wang et al 28 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Wu et al 21 reported that the grain size declined with increasing gas flow, the highest grain size was 33.72 nm, recorded at 40 sccm, and that it decreased to 18 sccm for a flow rate of 60 sccm argon flow rate. The decrease in grain size from 28.85 to 23.43 nm with the rise in argon flow rate from 10 to 30 sccm was also observed by Shain et al 23 . A similar increase in grain size of thin films from 6.3 to 14.8 nm with a decrease in argon flow rate was also observed by Wang et al 28 .…”
Section: Resultssupporting
confidence: 78%
“…Similarly, a maximum intensity of (002) peak was observed at 0.3 Pa which gradually decreased with increase in the argon gas flow rate 22 . Shain et al 23 observed (002) peak of ZnO when deposited AZO thin films by changing argon pressure from 10 to 30 sccm, moreover, they noticed that there was no impurity of aluminium seen in XRD patterns, and with the rise in argon pressure, the intensity of the peak diminished. The increase in the intensity of the (002) peak with the decrease in the argon partial pressure were also observed by other researchers [24][25][26] .…”
Section: Resultsmentioning
confidence: 99%